The formulation of the foundations for probabilistic modeling and evaluation of medical service quality - Чабан, Олеся Петрівна (Technology audit and production reserves, 2014)
Analyzes of theoretical and applied aspects in the construction of decision support systems and peculiarities of decision making process in medicine is given in the article. The elements of information system (IS) for medical field are made on the results of work. Conditions for the automatic selection of the optimal algorithm for solving the problem of patient diagnosing are made in this system with the help of the domain model (ontology) and an adequate knowledge base. It is found that the results of the system design of decision support and making for treatment decisions with the system of relations for quality estimation of diagnosis procedure based on functional qualities give a physician the opportunity to raise the level of skilled care and effectiveness of drug therapy choice for treatment of various disease types of patients.